Infant exposure to Fluvoxamine through placenta and human milk: a case series - A contribution from the ConcePTION project - Monfort, Anaëlle; Cardoso, Evelina; Eap, Chin B.; Fischer Fumeaux, Céline J.; Graz, Myriam Bickle; Morisod Harari, Mathilde; Weisskopf, Etienne; Gandia, Peggy; Allegaert, Karel; Nordeng, Hedvig; Hascoët, Jean-Michel; Claris, Olivier; et al. (Frontiers in Psychiatry, 2023)
Introduction: Fluvoxamine is widely used to treat depression during pregnancy and lactation. However, limited data are available on its transfer to the fetus or in human milk. This case series provides additional information on the infant exposure to fluvoxamine during pregnancy and lactation. Case presentation: Two women, aged 38 and 34 years, diagnosed with depression were treated with 50 mg fluvoxamine during pregnancy and lactation. At delivery a paired maternal and cord blood sample was collected for each woman. The first mother exclusively breastfed her child for 4 months and gave one foremilk and one hindmilk sample at 2 days and 4 weeks post-partum, whereas the second mother did not breastfeed. Results: The cord to plasma concentration ratios were 0.62 and 0.48, respectively. At two weeks post-partum, relative infant doses (RID) were 0.47% and 0.57% based on fluvoxamine concentrations in foremilk and hindmilk, respectively. At 4 weeks post-partum, the RIDs were 0.35% and 0.90%, respectively. The child from the first mother was born healthy and showed a normal development at the 6th, 18th and 36th month follow-ups. One of the twins from the second woman was hospitalized for hypoglycemia that was attributed to gestational diabetes and low birth weight. The second one was born healthy. Conclusion: These results suggest a minimal exposure to fluvoxamine during lactation which is in accordance with previously published data. Larger clinical and pharmacokinetic studies assessing the long-term safety of this drug during lactation and the variability of its exposure through breastmilk are warranted.